Sugar gliders - Boruchowitz, David E. (Animal Planet Pet Care Library., 2012)
While sugar gliders might look like furry extraterrestrials, they are actually opossum-like mammals that make fascinating pets. Sugar gliders do actually glide--often landing on top of their owner's head! Although sugar gliders--sometimes called sugar bears--are naturally found in Australia, the ones sold as pets come from domestic breeders. Once bonded to their owners, these pint-sized companions are content to ride in pockets or on shoulders. Sugar gliders do require more care than most other small mammals, but dedicated owners will not have trouble meeting their needs. This expertly written guide provides sugar glider owners with the necessary information to house, feed, handle, groom, and understand these charming creatures, and it contains numerous photos, sidebars, and tip boxes that enhance the text.